Chemistry in context applying chemistry to society - Middlecamp, Catherine (McGraw-Hill, 2012)
Following in the tradition of the first six editions, the goal of this successful, issues-based textbook, Chemistry in Context, seventh edition, is to establish chemical principles on a need-to-know basis for non-science majors, enabling them to learn chemistry in the context of their own lives and significant issues facing science and the world. The non traditional approach of Chemistry in Context reflects today's technological issues and the chemistry principles imbedded within them. The seventh edition applies sustainability principles wherever possible. Global warming, alternate fuels, nutrition, and genetic engineering are examples of issues that are covered in Chemistry in Context.